A Study to Assess the Effectiveness of Plan Teaching Program on Knowledge Regarding Newborn Care among Postnatal Mothers - J. Patel, Rupal; G. , Bindhumol; S Pavagadhi, Miteesha; B. Patel, Krupa; M. Damor, Aarti; I. Dudhwala, Mujib (International Journal of Psychosocial Rehabilitation, 2020)
Background of the study: The newborn’s arrival is one of the most fabulous moments of life for the parents and family. Principally, the mother is the primary person to take more responsibility to care for the precious gift of the newborn in order to reduce the mortality and morbidity. The global issue of neonatal mortality rate is approximately more than 3.3 million in the world. According to the World Health Organization, only five countries account for more than half of newborn deaths, viz., India, Nigeria, Pakistan, China, and the Democratic Republic of Congo. 98% of neonatal mortalities occur in developing regions, 28% in the least developed countries. In India, out of 26 million babies born, around 0.75 million newborns die every year; it’s the highest for any country in the world. Among these, 56 % occur mainly in Uttar Pradesh, Madhya Pradesh, Bihar, Rajasthan, Andhra Pradesh, and Telangana. Aim of the study: The present study aimed to assess the knowledge regarding new care among postnatal mothers Material and methods: In this study, an evaluative research approach was used with a pre-experimental one-group pretest-posttest research design. The sampling technique was non-probability convenience sampling used to collect the data from 40 samples of postnatal mothers, and data collection was done by administering the structured questionnaire. Descriptive and inferential statistics were used to analyze the data, such as frequency, percentage, and chi-square test. Results: In the pretest, 28% of samples had an inadequate level of knowledge, 72% of samples had an adequate level of knowledge, and 00% of samples had an excellent level of knowledge regarding newborn care. So, it revealed that they need the newborn care knowledge to overcome the poor knowledge level. In the posttest, 5% of samples were having inadequate knowledge, 18% of samples were having adequate knowledge, and 77% of samples were having excellent knowledge levels for newborn care. The chi-square was used to identify the association between selected demographic variables and level of knowledge at a significance level of 0.05. According to the demographic variable of age of mother, education, parity, type of delivery, age of child, type of family, and weight of child were non-significant at the 0.05 level of significance. Conclusion: The purpose of the study was to evaluate the effectiveness of the plan teaching program among 40 postnatal mothers. The finding of the study concluded that the majority of postnatal mothers had an inadequate level of knowledge. The planned teaching program was effective among postnatal mothers in improving knowledge significantly at the 0.05 level regarding newborn care.